1998
DOI: 10.1111/j.1574-0862.1998.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Farm size, productivity and returns to scale in agriculture revisited: a case study of wine producers in South Africa

Abstract: The inverse relationship between farm size and productivity has almost become a 'stylised fact' in the economic development literature. Most of the studies contributing to this preception have been flawed by methodological shortcomings and the request is that these studies be treated with caution. Using recent farm survey data from the wine producing areas of the Western Cape of South Africa, this study attempts to overcome some of the methodological problems, distinguishing between partial and total productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 7 publications
1
26
0
1
Order By: Relevance
“…The quartile of smallest farms has an average efficiency of 65%, the next quartile 71%, the next 75% and the largest 76%, so the scale effects are relaively unimportant, when judged according to land area. This conforms with the only previous study of scale efficiency in wine grape production, by Townsend, Kirsten and Vink (1998), which found no consitent relationship between yield, labour productivity, or total factor productivity and farm size, which was measured by area or number of workers. In their Robertson and Worcester samples, the small and medium sized farms were often more efficienct than the largest farms.…”
Section: Stochastic Production Function and Inefficiency Model Resultssupporting
confidence: 92%
“…The quartile of smallest farms has an average efficiency of 65%, the next quartile 71%, the next 75% and the largest 76%, so the scale effects are relaively unimportant, when judged according to land area. This conforms with the only previous study of scale efficiency in wine grape production, by Townsend, Kirsten and Vink (1998), which found no consitent relationship between yield, labour productivity, or total factor productivity and farm size, which was measured by area or number of workers. In their Robertson and Worcester samples, the small and medium sized farms were often more efficienct than the largest farms.…”
Section: Stochastic Production Function and Inefficiency Model Resultssupporting
confidence: 92%
“…In general, the second stage is problematic since the statistical properties of the DEA efficiency score are not well known. Townsend et al (1998) report a negative relationship while Sharma et al (1 999) find a positive relationship. Page (1984) estimates the production frontier using econometric methods and calculated technical efficiency for four Indian manufacturing industries.…”
Section: Technical Efficiency and Size: A Review Of The Literaturementioning
confidence: 98%
“…This second step (Timmer, 1971) is pervasive in this literature. Two recent papers (Townsend et al, 1998;Sharma et al, 1999) analyse the relationship between technical efficiency and size using DEA. In both cases, the index of technical efficiency is regressed on a measure of size.…”
Section: Technical Efficiency and Size: A Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Using Cobb-Douglas stochastic functions, their empirical results show that farmers who participate in the programme are more technically efficient with mean technical efficiency equal to 94 per cent compared with those outside the project with mean efficiency equal to 79 per cent. Townsend et al (1998) using data envelopment analysis investigated the relationship between farm size, return to scale and productivity among wine producers in South Africa and found that most farmers operate under constant returns to scale, but the inverse relationship between farm size and productivity is weak. Weir (1999) investigated the effects of education on farmer productivity of cereal crops in rural Ethiopia using average and stochastic production functions.…”
Section: Introductionmentioning
confidence: 99%